2008
DOI: 10.1016/j.otohns.2008.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Does Microvascular free flap Reconstruction in oral Squamous cell Carcinoma Improve Patient Survival?

Abstract: A comparison between our study group and those of 3 previous similar studies would not provide definitive statistical evidence, but it could certainly suggest a trend. The comparison seems to support that microvascular free tissue transfer does not change the survival of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The results of this study indicated no statistical difference in the surgical margin when a free flap procedure was performed (coefficient, 0.789; 95% CI, À0.120 to 1.790; P = .099) These results are similar to other studies that have analyzed the surgical margin 14 and 5-year recurrence and survival rates 15,16 for free flap procedures.…”
Section: Non-statistically Meaningful Variablessupporting
confidence: 85%
“…The results of this study indicated no statistical difference in the surgical margin when a free flap procedure was performed (coefficient, 0.789; 95% CI, À0.120 to 1.790; P = .099) These results are similar to other studies that have analyzed the surgical margin 14 and 5-year recurrence and survival rates 15,16 for free flap procedures.…”
Section: Non-statistically Meaningful Variablessupporting
confidence: 85%
“…Various improvements in RT and chemotherapy regimens may have also had an impact on overall survival; however, the addition of postoperative chemotherapy is the only major shift in treatment in recent years. Modern surgical techniques allow reconstruction of more extensive defects, which could improve survival by allowing extirpative surgery in otherwise nonoperable patients or improving margin control in more extensive resections; however, the currently available literature is both limited and conflicting . We propose that the improvement in overall survival reflected in the national databases is at least partially because of the implementation of adjuvant CRT as a standard treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…The authors consider free flap reconstruction recommended, especially when postoperative functional deficits are expected (Mücke et al, 2010). A small study also designed to evaluate the impact of microsurgical reconstruction on survival didn't show any significant improvement only a trend towards better prognosis (Marchetti et al, 2008). This study didn't directly compare the results of free flaps and pectoralis major pedicled flaps.…”
Section: Oncologic Resultsmentioning
confidence: 99%